Sensorless control of fault tolerant PMSM drives in case of single-phase open circuit fault - Saleh, Kamel; Sumner, M. (2016)
This paper introduces a new method to track the saliency of a PMSM motor fed by a four-leg inverter in case of a single phase open circuit fault through measuring the dynamic current response of the motor line currents due the IGBT switching actions. In the case of a single phase open circuit fault, a fault-tolerant control strategy that includes taking appropriate actions to control the two remaining healthy currents, resulting in minor system performance degradation. The new strategy introduced in this paper includes software modifications only to the saliency tracking algorithm used in healthy mode to make it applicable to the reconfigured converter in the presence of a fault. The new method uses only the fundamental PWM waveform (i.e there is no modification to the operation of the four-leg inverter) similar to the fundamental PWM method proposed for a three-leg inverter. Simulation results are provided to verify effectiveness of the proposed strategy of saliency tracking of a PMSM motor driven by fault tolerant four-phase inverter over a wide speed ranges under the case of a single phase open circuit fault.